8x+(4-2)+3=3x-2(7+4x)+11

Simple and best practice solution for 8x+(4-2)+3=3x-2(7+4x)+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+(4-2)+3=3x-2(7+4x)+11 equation:



8x+(4-2)+3=3x-2(7+4x)+11
We move all terms to the left:
8x+(4-2)+3-(3x-2(7+4x)+11)=0
We add all the numbers together, and all the variables
8x-(3x-2(4x+7)+11)+3+2=0
We add all the numbers together, and all the variables
8x-(3x-2(4x+7)+11)+5=0
We calculate terms in parentheses: -(3x-2(4x+7)+11), so:
3x-2(4x+7)+11
We multiply parentheses
3x-8x-14+11
We add all the numbers together, and all the variables
-5x-3
Back to the equation:
-(-5x-3)
We get rid of parentheses
8x+5x+3+5=0
We add all the numbers together, and all the variables
13x+8=0
We move all terms containing x to the left, all other terms to the right
13x=-8
x=-8/13
x=-8/13

See similar equations:

| 3c-9=(-27) | | x(x+13)=-12 | | 6x6=36 | | 3.14x6x=4396 | | 5x+3(x+4)=9 | | 45x+80x=8040 | | 5-12y=3y | | 45+x+x=80 | | 50=2u+10 | | 1.4(y-5)-0.2=0.5(6y-8) | | 1x+72=32 | | Y=2.6x+3.1 | | 1/3(-9x-3)=11 | | 4d=3d–7 | | 4^(x+1)+2^(x+1)=72 | | 5^9/5^t=5^-3 | | 12*2(7r=)6 | | 2(-8-k)=-2k-11 | | 4x+5=9x-155x | | 11y=4÷11 | | |x-6|=8 | | Y=3x+-27 | | x+1/4=13 | | 3(5x−7)=24 | | 6x-2=5(4x+8) | | 2x(x-1)=x(x+1) | | 6(x-8)=2(x+6) | | 5x-(-4x)=-27 | | -4(-3y)-5y=21 | | x+1/5=4/5 | | 2(3x+5)=4(X+3)-4 | | 7x+5=-50 |

Equations solver categories